Pengaruh Pendidikan Agama pada Anak dalam Keluarga Beda Agama di Desa Klepu Sooko Ponorogo - Erwin Yudi Prahara (Cendekia: Kependidikan dan Kemasyarakatan, 2016)
This research aims to discuss a phenomenon of interfaith family in Klepu village, Sooko district, Ponorogo regency in the context of religious education transformation in family. This study was qualitative research. The subjects of the research are Islamic and catholic family, mixed faith family as well. The data were collected through observation, interview, and documentation. The result of the research indicates that mother religiosity is more dominant in influencing children’s religious upbringing. Nine informants showed that four cases of children religiosity follows religion of their mother, three cases of children religiosity follow religion of their father and father is religiously active, two cases of children religiosity is questionable because they are still baby. This situation happens because the family couple does not have agreement to be bound or there is an agreement containing a freedom for their children. This is because the communication between mother and children is more intense compared to father and children communication. Dominant figure of mother cannot be separated from her nurture and her more time to interact with her childrenحاولت هذه الدراسة عرض ظاهرة الأسرة الثنائية دينيا في قرية كليفو سوكو فونوروغو في سياق تحوّل التربية الدينية في الأسرة. اتّبعت هذه الدراسة المنهج الكيفي، ومصادر بياناتها الأسرة المسلمة والأسرة الكاتوليكية والأسرة الثنائية دينيا. أما أساليب جمع البيانات لهذا البحث فالملاحظة والمقابلة الشخصية والوثائق المكتوبة. دلت نتائج البحث على أن الأم وما تدين به تؤثّر كثيرا فيما يدين به الابن. ومن ستة المخبرين المبحوثين دلّت البيانات على أن أربعة منهم اتبعوا دين أمهم، وثلاثة منهم اتّبعوا دين أبيهم ( إذا كان الأب فعّالا في الأسرة )، واثنان منهم لم يكونا واضحين لكونهما في سن قبل الخامسة. وقعت هذه الحالة خاصة في الأسرة التي ليس فيها اتّفاق ملزم أو بين الزوجين اتّفاق ولكنّهما يعطيان الحريّة للأبناء في اختيار الدين. وقعت هذه الظاهرة لأن كمية الاتصال بين الأبناء وبين الأم أكثر من كمية الاتصال بينهم وبين آبائهم.  كانت هيمنة الأم في الأسرة لا تنفصل عن كونها أما للأبناء وطول اتصالها بالأبناء.